2022
DOI: 10.1002/adhm.202102185
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of A Membrane‐Anchored Probe for Multidimensional Quantification of Endocytic Dynamics

Abstract: As a process of cellular uptake, endocytosis, with gradient acidity in different endocytic vesicles, is vital for the homeostasis of intracellular nutrients and other functions. To study the dynamics of endocytic pathway, a membrane-anchored pH probe, ECGreen, is synthesized to visualize endocytic vesicles under structured illumination microscopy (SIM), a super-resolution technology. Being sensitive to acidity with increasing fluorescence at low pH, ECGreen can differentiate early and late endosomes as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…[13] To investigate the behavior of lysosomes during this process, we induced mitophagy, a form of autophagy that selectively degrades damaged mitochondria, by damaging mitochondria with carbonyl cyanide m -chlorophenyl hydrazone (CCCP), a common mitophagy inducer. [8b, 14] After treating HeLa cells with CCCP for 12 h, we observed that the shape of the mitochondria stained with MitoTracker Deep Red (MTDR) significantly changed and became shorter and more rounded (Figure 3A), and damaged mitochondria also lost their cristae in the inner membrane (Figures 3B and 3C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] To investigate the behavior of lysosomes during this process, we induced mitophagy, a form of autophagy that selectively degrades damaged mitochondria, by damaging mitochondria with carbonyl cyanide m -chlorophenyl hydrazone (CCCP), a common mitophagy inducer. [8b, 14] After treating HeLa cells with CCCP for 12 h, we observed that the shape of the mitochondria stained with MitoTracker Deep Red (MTDR) significantly changed and became shorter and more rounded (Figure 3A), and damaged mitochondria also lost their cristae in the inner membrane (Figures 3B and 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the strong connection between mitochondria and lysosomes, we exploited patient-derived SLC25A46 mutant fibroblasts; this led to highly fused mitochondria and decreased mitochondrial oxidative phosphorylation and resulted in clinical symptoms of mitochondrial diseases. [8g] This gene encodes a mitochondrial solute carrier protein family member, and its mutation results in neuropathy and optic atrophy. Even though the cell shapes of the SLC25A46 mutant fibroblasts were not different from the wild type (WT) (Figure S17), the mitochondria were relatively longer than those in the WT fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the induction of MLCs could potentially be used to accelerate mitochondrial fission. However, a method to directly regulate MLCs in a reversible and controllable manner in living cells is critical 29 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available lysosomal dyes (e.g., LTR) are acidic pH-dependent and are repelled by lysosomes as their pH value increases. 27 Because nanoparticles enter lysosomes via endocytosis, the localization of the BSA−NCs was not expected to change with pH fluctuation. To gauge that difference between commercial dyes and the BSA−NCs, the stained cells were treated with chloroquine (100 μM, 30 min), which is a cell-permeable base, to increase the lysosomal pH.…”
mentioning
confidence: 99%